Examining the Impacts of GDP, Trade Openness, Freedom Index and the Internet on FDI: Comparison of Countries with Panel ARDL - Guz, Tugba; Parim, Coskun; Cene, Erhan (Prague Univ Economics and Business, 2025)
The main purpose of this study is to examine the impacts of GDP, trade openness, the freedom index and the internet on FDI in 54 countries, including developing, transition and developed countries, over the period 1995-2021. First, the variables affecting FDI are determined. Then, first- and second-generation unit root tests are conducted for panel data to investigate stationarity. Finally, long- and short-run relationships between variables that have an effect on FDI are exhibited with panel cointegration tests and panel ARDL analysis. Among 17 candidate variables, internet, GDP, the freedom index and trade openness are determined to affect FDI. GDP, the internet and the freedom index have a significant positive and trade openness has a significant negative relationship with FDI in the short run. Finally, there is a long-term equilibrium between FDI and all the variables. Trade openness also has negative coefficient in developing countries such as China, Brazil and Turkey. This is a unique study in which empirical findings are given for each country with the PMG model, which would aid the policy implications identified for the 54 countries, including developing, transition and developed countries.
Keywords: Foreign direct investment; GDP; trade openness; freedom index; internet; panel ARDL; FOREIGN DIRECT-INVESTMENT; UNIT-ROOT TESTS; HETEROGENEOUS PANELS; ECONOMIC-FREEDOM; DETERMINANTS; COINTEGRATION; GROWTH; Business & Economics; Government & Law